Outcomes of acutely ill older hospitalised patients following implementation of tailored models of care: a repeated measures (pre and post intervention) design - Chang, E.; Hancock, K.; Hickman, L.; Glasson, J.; Davidson, Patricia (Elsevier Science, 2007)
Background: There is a lack of research investigating models of nursing care for older hospitalised patients that address the nursing needs of this group. Objectives: The objective of this study is to evaluate the efficacy of models of care for acutely older patients tailored to two contexts: an aged care specific ward and a medical ward. Design: This is a repeated measures design. Efficacy of the models was evaluated in terms of: patient and nurses’ satisfaction with care provided; increased activities of daily living; reduced unplanned hospital readmissions; and medication knowledge. Settings: An aged care specific ward and a medical ward in two Sydney teaching hospitals. Participants: There were two groups of patients aged 65 years or older who were admitted to hospital for an acute illness: those admitted prior to model implementation (n ¼ 232) and those admitted during model implementation (n ¼ 116). Patients with moderate or severe dementia were excluded. The two groups of nurses were the pre-model group (n ¼ 90) who were working on the medical and aged care wards for the study prior to model implementation, and the post-model group (n ¼ 22), who were the nurses working on the wards during model implementation. Methods: Action research was used to develop the models of care in two wards: one for an aged care specific ward and another for a general medical ward where older patients were admitted. The models developed were based on empirical data gathered in an earlier phase of this study. Results: The models were successful in both wards in terms of increasing satisfaction levels in patients and nurses (po0.001), increasing functional independence as measured by activities of daily living (po0.01), and increasing medication knowledge (po0.001). Conclusions: Findings indicate that models of care developed by nurses using an evidence-based action research strategy can enhance both satisfaction and health outcomes in older patients.